Effect of thermal state and thermal comfort on cycling performance in the heat - Schulze, E.; Daanen, H. A. M.; Levels, K.; Casadio, J. R.; Plews, D. J.; Kilding, A. E.; Siegel, R.; Laursen, P. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To determine the effect of thermal state and thermal comfort on cycling performance in the heat. Methods: Seven well-trained male triathletes completed 3 performance trials consisting of 60 min cycling at a fixed rating of perceived exertion (14) followed immediately by a 20-km time trial in hot (30°C) and humid (80% relative humidity) conditions. In a randomized order, cyclists either drank ambient-temperature (30°C) fluid ad libitum during exercise (CON), drank ice slurry (-1°C) ad libitum during exercise (ICE), or precooled with iced towels and ice slurry ingestion (15g/kg) before drinking ice slurry ad libitum during exercise (PC+ICE). Power output, rectal temperature, and ratings of thermal comfort were measured. Results: Overall mean power output was possibly higher in ICE (+1.4% ± 1.8% [90% confidence limit]; 0.4 > smallest worthwhile change [SWC]) and likely higher PC+ICE (+2.5% ± 1.9%; 1.5 > SWC) than in CON; however, no substantial differences were shown between PC+ICE and ICE (unclear). Time-trial performance was likely enhanced in ICE compared with CON (+2.4% ± 2.7%; 1.4 > SWC) and PC+ICE (+2.9% ± 3.2%; 1.9 > SWC). Differences in mean rectal temperature during exercise were unclear between trials. Ratings of thermal comfort were likely and very likely lower during exercise in ICE and PC+ICE, respectively, than in CON. Conclusions: While PC+ICE had a stronger effect on mean power output compared with CON than ICE did, the ICE strategy enhanced late-stage time-trial performance the most. Findings suggest that thermal comfort may be as important as thermal state for maximizing performance in the heat.